Indigenous Knowledge and Sustainable Resource Management - A Bibliometric Review - Borolla, Fridolin Vrosansen; Rahmayanti, Henita; Hidayat, Otib Satibi; Abdullah, Khairul Hafezad (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
The centuries-old methods of Indigenous cultures can help us manage resources sustainably and live in harmony with the environment. This study aims to identify publication trends on Indigenous knowledge and sustainable resource management. The current bibliometric review employed Scopus and Web of Science (WoS) datasets and analysed using ScientoPy and VOSviewer to discover the publications’ trends. The results of this review identified that the evolution of publications fluctuated and that the initiative to increase the research on this topic is crucial. Based on keywords analysis, this study found that “Ethnobotany” and “Climate Change” are used differently, highlighting the growing importance of Indigenous viewpoints in tackling modern environmental concerns and reflecting the dynamic nature of research goals. The international network collaboration indicated that a four-country collaboration exist where Indonesia had a strong network with England and Finland. Future Indigenous knowledge and sustainable resource management research should examine contextual factors that affect publication patterns to build on these findings. The causes of the highest publishing years and database discrepancies may be examined. A detailed analysis of research activity changes can help explain this field’s research trend.